THE FACTORS AFFECT TOEIC PASSING GRADES IN TOEIC INTENSIVE COURSE FOR THIRD YEAR STUDENTS - Ari Satria; Safra Apriani Zahraa (Politeknik Negeri Bengkalis, 2018)
This study is expected to provide an overview of the factors that affect TOEIC Passing Grades in TOEIC Intensive Course for Final Year Students. The purpose of this study is to conduct an empirical investigation whether the internal factor variable and external factors affect the variable of passing grade. The total populations in this study were 150 respondents. The data were collected through questionnaires. Data analysis was done by multiple regression using SPSS version 22. The result showed that internal factor had an effect on student's learning achievement, while external factor had no influence to the TOEIC passing grades.Â Keywords : Internal, external, intensive, TOEIC